Urban-Hist, le patrimoine toulousain à la carte - Catherine Bernard; Marc Comelongue; Louise-Emmanuelle Friquart; Laure Krispin; Géraud de Lavedan; Laure Moreau (Les Cahiers de Framespa)
Since 2003, the Archives municipales de Toulouse have developed a website integrating interactive spatial data, and are permanently updating it with new data on Toulouse’s heritage, thus making of Urban-Hist a tool that allows furthering our knowledge of the town.Data do include archaeological researches, archives documents, as well as the whole results of the Inventaire’s mission on buildings’heritage.All in a single application, Urban-Hist different interfaces have different purposes: acquiring new historical data and allowing the administrators to manage and update them daily, whilst in the meantime the public has access to its whole content. This is why the new version of Urban-Hist is made of two distinct elements: Urban-Hist Gestion and Urban-Hist Publication.Knowing our territories via a Spatial Data Infrastructure will help to understand the shape and evolution of the town, and will help foreseeing and planning the future of it.